TINJAUAN KRIMINOLOGIS TERHADAP PELAKU IKLAN JUDI ONLINE MELALUI MEDIA SOSIAL INSTAGRAM - Tefa, Ruben E.; Amalo, Heryanto; Dima, Adrianus Djara (The Juris, 2025)
Human life today has been in an era where it has been dominated by massive technological developments, and one of them is in the field of communication and information. The presence of a major innovation, namely the internet network, brings so many conveniences and benefits in the world of communication and information. However, this development is also not free from adverse effects, namely crimes that are influenced by irresponsible behavior carried out by humans in utilizing existing developments. The new crime caused by this development is the dissemination of information in the form of advertisements about online gambling which occurs so much through digital communication and information platforms such as Instagram social media. The objectives of this research are: (1) to find out what factors cause the involvement of online gambling advertisers through social media (Instagram) in Kupang City. (2) To find out how the countermeasures against online gambling advertisements through social media (Instagram) in Kupang City. This research is empirical research with a legal sociological approach method so that it is based on data obtained in the field through interviews with 12 respondents. This data is analyzed descriptively-qualitatively. The results showed that: (1) factors causing online gambling advertisements through social media (Instagram) in Kupang City are lifestyle, minimal skills, weak law enforcement, circle of friends, and family environment. (2) Countermeasures against online gambling advertisements through social media (Instagram) in Kupang City at this time are still only in the form of preventive countermeasures carried out by the Kupang City Resor Police Agency.